Photovoltaic wastewater treatment agent and preparation method thereof

By introducing cerium salt, iron salt, zirconium salt and lanthanum salt into modified alumina to form a Fe-Zr-La trimetallic modification system, and using a specific surfactant, Ce-doped alumina material with oxygen vacancy structure was prepared, which solved the problems of low defluorination efficiency and poor stability in photovoltaic wastewater treatment, and achieved efficient and stable fluoride ion removal effect.

CN120885187AActive Publication Date: 2025-11-04ORDOS SHENGYUAN WATER GRP CO LTD

Patent Information

Application Number
CN202511394707.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-11-04
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

Existing photovoltaic wastewater treatment methods suffer from low defluorination efficiency, high cost, and poor stability. In particular, in the treatment of high-concentration fluoride-containing wastewater, traditional adsorbents such as activated alumina have problems such as small specific surface area, poor selectivity, and low mechanical strength.

Method used

Based on modified alumina, a Fe-Zr-La trimetallic modification system was formed by introducing cerium salt, iron salt, zirconium salt and lanthanum salt. Combined with sodium maleic anhydride-octadecylamide-dicarboxylate and sodium itaconic acid-based asymmetric diester sulfonate as surfactants, a photovoltaic wastewater treatment agent was prepared, forming a Ce-doped alumina material with an oxygen vacancy structure, which enhances the adsorption performance and stability of fluoride ions.

Benefits of technology

It significantly improved the electrostatic adsorption capacity for fluoride ions and the stability under high acid and alkaline environments, thereby enhancing the efficiency and stability of photovoltaic wastewater treatment. It achieved multi-mechanism, highly selective synergistic removal of fluoride, reducing the fluoride content in wastewater to below 0.4 mg/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120885187A_ABST
    Figure CN120885187A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wastewater treatment agents, and discloses a photovoltaic wastewater treatment agent and a preparation method thereof.The preparation method of the treatment agent comprises the following steps that aluminum salt and cerium salt are dispersed in deionized water, then a surfactant is added, and a precursor is obtained after even mixing; adding sodium hydroxide into the precursor to adjust the pH value to 7.5-8.5, aging, centrifuging, washing, drying and calcining to obtain modified aluminum oxide; ultrasonically dispersing the modified aluminum oxide in deionized water, sequentially adding ferric salt, zircon salt and lanthanum salt, uniformly mixing, performing hydrothermal reaction, and cooling, centrifuging, washing and drying a product to obtain the photovoltaic wastewater treatment agent. The wastewater treatment agent disclosed by the invention has excellent fluorine removal performance and can be used for purifying photovoltaic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of wastewater treatment agents, in particular to a photovoltaic wastewater treatment agent and a preparation method thereof. BACKGROUND

[0002] With the rapid development of the photovoltaic industry, a large number of photovoltaic components will generate complex wastewater containing high concentrations of fluorine, heavy metals and organic complexes in the process of cleaning, etching, electroplating and the like. Such wastewater has the characteristics of complex composition, large pH fluctuation, strong toxicity and poor biodegradability. If it is not effectively treated and directly discharged, it will pose a serious threat to the ecological environment and water safety.

[0003] There are many studies on the treatment of fluorine-containing water bodies at present, and the methods differ due to different components and contents. The main methods include adsorption, chemical precipitation and biological degradation. Although these methods can achieve certain water treatment effects, they also have some shortcomings. The fluorine removal process based on the precipitation process is suitable for the treatment of water bodies with high fluorine concentration, but this process has high requirements for the pH value of the water to be treated, a large amount of toxic sludge is generated during the treatment process, and the removal rate is often low. Traditional adsorption methods, especially activated alumina, have good adsorption effects, but the regeneration technology of adsorbents is expensive, which limits the application of adsorption processes in the field of high-fluorine water treatment. There are many methods for treating fluorine-containing water, and the commonly used methods at home and abroad can be roughly divided into two categories, namely precipitation method and adsorption method. In addition to these two types of processes, there are freezing method, ion exchange resin defluorination method, activated carbon defluorination method, ultrafiltration defluorination method, and electrodialysis, but they have been rarely applied in defluorination processes so far, mainly because of high cost and low defluorination rate.

[0004] The common precipitation methods include chemical precipitation and flocculation precipitation. Among them, the chemical precipitation method is mainly used for the treatment of high-concentration fluorine-containing wastewater. The commonly used method is calcium salt precipitation, i.e. lime precipitation, which adds calcium salt and other chemicals to the wastewater to make calcium ions react with fluorine ions to generate CaF2 precipitate, so as to remove fluorine in the wastewater. This process is simple and convenient, and the cost is low, but the calcium fluoride precipitate generated in the commonly used lime precipitation defluorination method will wrap the surface of Ca(OH)2 particles, so they cannot be fully utilized, and therefore an excessive amount of Ca(OH)2 needs to be added, which not only increases the sludge production, but also reduces the purity of fluorine-containing sludge. 2+ However, a large amount of calcium salt is mixed into the sludge, which not only increases the sludge production, but also reduces the purity of fluorine-containing sludge. At the same time, the fluorine content in the treated wastewater is more than 20 mg / L, so this method is not suitable for the treatment of F - Low drinking water. During the treatment of wastewater by flocculation precipitation method, very fine particles are easily generated, which have small specific gravity and large viscosity, and are in a colloidal state during the precipitation process, so they are difficult to separate. After the flocculant is added, the pH value of the water is significantly reduced due to the hydrolysis of cations (such as Al 3+ ), which easily causes acidic water, which is not suitable for drinking.

[0005] Adsorption method is the most concerned method due to its simple operation, low cost, convenience and other advantages. Activated carbon, alumina, silica gel, zeolite and other materials are often used in adsorption method. However, the traditional alumina adsorbent has problems such as small specific surface area, poor selectivity, low mechanical strength, limited adsorption capacity, and poor stability under high salinity and strong acid and alkali conditions, which leads to unstable treatment efficiency.

[0006] Therefore, it is urgent to develop a new photovoltaic wastewater treatment material with stable structure and excellent adsorption performance to meet the actual treatment needs of high-concentration wastewater in the photovoltaic industry. SUMMARY

[0007] Based on the technical problems existing in the background art, the present application provides a photovoltaic wastewater treatment agent and a preparation method thereof. The wastewater treatment agent has excellent defluorination performance and can be used for purifying photovoltaic wastewater.

[0008] The preparation method of the photovoltaic wastewater treatment agent provided by the present application is as follows: S1: preparation of modified alumina; S2: dispersing the modified alumina in deionized water, then adding iron salt, zirconium salt and lanthanum salt in sequence, mixing uniformly, and then hydrothermal reaction, and the product is obtained after cooling, centrifugation, washing and drying.

[0009] Preferably, the preparation method of the modified alumina is as follows: S11: dispersing aluminum salt and cerium salt in deionized water, then adding surfactant, mixing uniformly to obtain a precursor; S12: adding sodium hydroxide to the precursor to adjust the pH to 7.5-8.5, and then aging, centrifugation, washing, drying and calcination to obtain modified alumina.

[0010] Preferably, the aluminum salt is one or more of aluminum nitrate and its hydrate, aluminum chloride and its hydrate, and aluminum sulfate and its hydrate.

[0011] Preferably, the cerium salt is one or more of cerium nitrate and its hydrate, cerium chloride and its hydrate, and cerium sulfate and its hydrate.

[0012] Preferably, the mass ratio of aluminum salt, cerium salt and surfactant is 1:0.05-0.15:0.01-0.1.

[0013] Preferably, the aging condition is: temperature 60-70℃, time 4-8h.

[0014] Preferably, the calcination condition is: temperature 400-600℃, time 2-4h, and heating rate 3-7℃ / min.

[0015] Preferably, the surfactant is composed of sodium maleopimarate octadecanamide dicarboxylate and sodium itaconate-based asymmetric diester sulfonate in a mass ratio of 2:1-4.

[0016] Preferably, the mass ratio of the modified alumina, iron salt, zirconium salt and lanthanum salt is 1:0.05-0.15:0.05-0.1:0.05-0.15.

[0017] Preferably, the iron salt is one or more of ferric nitrate and its hydrate, ferric chloride and its hydrate, and ferric sulfate and its hydrate.

[0018] Preferably, the zirconium salt is one or more of zirconium nitrate and its hydrate, zirconium chloride and its hydrate, and zirconium oxychloride and its hydrate.

[0019] Preferably, the lanthanum salt is one or more of lanthanum nitrate and its hydrate, and lanthanum chloride and its hydrate.

[0020] Preferably, the temperature of the hydrothermal reaction is 140-160℃, and the time is 4-8h.

[0021] The photovoltaic wastewater treatment agent provided by the present application is prepared by the above preparation method.

[0022] The beneficial technical effects of the present application are: (1) The present application introduces cerium salt as a doping source in the modified alumina precursor, which can form Ce-doped alumina material with oxygen vacancy structure in the subsequent calcination process. The reversible oxidation-reduction characteristics of Ce 3+ / Ce 4+ endow the material with excellent electron transfer ability, enhance the complexation and exchange ability of heavy metal ions; at the same time, the doping of cerium helps to improve the crystal structure stability of alumina particles, significantly improves its corrosion resistance and thermal stability in high acid-base environment, thereby prolonging the service life of the adsorbent in the photovoltaic wastewater treatment process. In addition, the addition of Ce element also increases the density of the surface acid sites of the adsorbent, and enhances its electrostatic adsorption capacity for anions such as fluoride ions.

[0023] (2) The present application introduces sodium maleopimarate octadecanamide dicarboxylate and sodium itaconate-based asymmetric diester sulfonate as surfactants into the precursor solution, which significantly improves the dispersibility of the particles and the pore structure regulation ability. The surfactant of the present application can inhibit particle agglomeration through steric hindrance and electrostatic repulsion, making the modified alumina nanoparticles more uniform in size and higher in specific surface area; on the other hand, it can form weak coordination with metal ions, inducing the formation of more ordered and cooperative framework structure in the hydrothermal reaction, thereby improving the multi-component synergistic adsorption performance of the subsequent composite material.

[0024] (3) The Fe-Zr-La three-metal modified system is formed by compounding modified alumina with iron salt, zirconium salt and lanthanum salt, and a variety of active sites and composite oxide synergistic networks can be generated on the material surface. Iron element mainly exists in Fe(III) oxidation state, has excellent coordination ability and flocculation effect; zirconium element has high affinity for fluorine ions, and the Zr-OH functional group formed by the introduction of zirconium element can significantly enhance the specific adsorption of fluorine; lanthanum, as a typical rare earth element, has adsorption selectivity for a variety of anions, and at the same time enhances the overall acid and alkali corrosion resistance of the material. The synergistic loading and distribution of the three on the modified alumina carrier make the material surface present diversified functional sites, realize the multi-mechanism and high-selectivity synergistic removal of fluorine in photovoltaic wastewater, and greatly improve the overall treatment efficiency and stability. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 The SEM images of the treating agent proposed in the application at different proportions are shown in the figure, wherein (a) is 20 μm, (b) is 10 μm, (c) is 5 μm, and (d) is 2 μm. Figure 2 The SEM images of the treating agent proposed in the application after adsorption at different proportions are shown in the figure, wherein (a) is 20 μm, (b) is 10 μm, (c) is 5 μm, and (d) is 2 μm. DETAILED DESCRIPTION

[0026] The application will be further described below in combination with specific embodiments.

[0027] The preparation method of the sodium maleopimaric acid octadecylamide double carboxylic acid in the embodiment of the application is as follows: 30 g of maleopimaric acid, 20 g of octadecylamine and 0.8 g of triethylamine are dispersed in anhydrous ethanol, and after reaction at room temperature for 4 h, NaOH ethanol-water solution is added, and reaction is carried out at 55 ℃ for 5 h. After reaction, filtration and concentration are carried out to obtain sodium maleopimaric acid octadecylamide double carboxylic acid. The specific structural formula is as follows:

[0028] The preparation method of the sodium itaconic acid-based asymmetric double ester sulfonic acid is as follows: 0.11 mol of lauryl alcohol polyoxyethylene ether (AEO-7), 0.35 g of p-toluene sulfonic acid, 0.12 g of hydroquinone and 0.1 mol of itaconic anhydride are mixed and heated to reflux for reaction for 3 h to obtain an intermediate product I; 0.1 mol of the intermediate product I, 1 g of p-toluenesulfonic acid and 0.15 mol of lauric acid monoethanolamide are mixed and heated to reflux for reaction for 5 h to obtain an intermediate product II; 0.1 mol of the intermediate product II, 0.12 mol of sodium bisulfite aqueous solution and cetyltrimethylammonium bromide (1% of the mass of the intermediate product II) are mixed and heated to reflux for reaction for 3 h, and after washing and reduced pressure distillation, the sodium itaconic acid-based asymmetric double ester sulfonic acid is obtained. The specific structural formula is as follows: .

[0029] Example 1 Al(NO3)3·9H2O and Ce(NO3)3·6H2O were dispersed in deionized water, and then a surfactant was added. After mixing, a precursor was obtained. Sodium hydroxide was added to the precursor to adjust the pH to 8. After aging, centrifugation, washing, drying, and calcination, modified alumina was obtained.

[0030] The modified alumina was ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O, and La(NO3)3·6H2O were added in sequence. After mixing, a hydrothermal reaction was carried out. After cooling, centrifugation, washing, and drying, a photovoltaic wastewater treatment agent was obtained.

[0031] The mass ratio of Al(NO3)3·9H2O, Ce(NO3)3·6H2O, and the surfactant was 1:0.1:0.05. The aging conditions were a temperature of 65℃ and a time of 6h. The calcination conditions were a temperature of 500℃, a time of 3h, and a heating rate of 5℃ / min.

[0032] The surfactant was composed of maleopimaric acid octadecyl amide sodium dicarboxylate and itaconic acid-based asymmetric diester sodium sulfonate at a mass ratio of 1:1.

[0033] The mass ratio of modified alumina, FeCl3·6H2O, ZrOCl2·8H2O, and La(NO3)3·6H2O was 1:0.1:0.08:0.1. The hydrothermal reaction temperature was 150℃, and the time was 6h.

[0034] Figure 1 The SEM images of the treatment agent prepared in this example under different magnifications showed a core-shell structure, and a large number of large pores were produced, the specific surface area was greatly increased, more adsorption sites were provided for fluoride ions, and the removal of fluoride in water was facilitated.

[0035] Figure 2 The SEM images of the treatment agent prepared in this example after adsorption under different magnifications showed that the surface of the reacted material was wrapped in a layer of material, and a large number of fine particles were adsorbed, the pore size was filled with these particles, forming a complex. Its surface was smoother than that of the material before reaction, and the complex structure was more compact. It was speculated that the defluorination mechanism included surface adsorption-complexation. Example 2

[0036] Al(NO3)3·9H2O and Ce(NO3)3·6H2O were dispersed in deionized water, and then a surfactant was added. After mixing, a precursor was obtained. Sodium hydroxide was added to the precursor to adjust the pH to 7.5. After aging, centrifugation, washing, drying, and calcination, modified alumina was obtained.

[0037] The modified alumina is ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O are sequentially added and uniformly mixed, and then a hydrothermal reaction is performed, and the product is obtained after cooling, centrifugation, washing and drying.

[0038] The mass ratio of Al(NO3)3·9H2O, Ce(NO3)3·6H2O and the surfactant is 1:0.05:0.01; the aging condition is 60℃ for 8h; and the calcination condition is 400℃ for 4h with a temperature rising rate of 3℃ / min.

[0039] The surfactant is composed of maleopimaric acid octadecyl amide double carboxylic acid sodium and itaconic acid-based asymmetric double ester sulfonic acid sodium with a mass ratio of 2:1.

[0040] The mass ratio of the modified alumina, FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O is 1:0.05:0.05:0.05; the hydrothermal reaction temperature is 140℃, and the time is 8h. Example 3

[0041] Al(NO3)3·9H2O and Ce(NO3)3·6H2O are dispersed in deionized water, and then the surfactant is added, and the precursor is obtained after uniform mixing; sodium hydroxide is added in the precursor to adjust the pH to 8.5, and the modified alumina is obtained after aging, centrifugation, washing, drying and calcination.

[0042] The modified alumina is ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O are sequentially added and uniformly mixed, and then a hydrothermal reaction is performed, and the product is obtained after cooling, centrifugation, washing and drying.

[0043] The mass ratio of Al(NO3)3·9H2O, Ce(NO3)3·6H2O and the surfactant is 1:0.15:0.1; the aging condition is 70℃ for 4h; and the calcination condition is 600℃ for 2h with a temperature rising rate of 7℃ / min.

[0044] The surfactant is composed of maleopimaric acid octadecyl amide double carboxylic acid sodium and itaconic acid-based asymmetric double ester sulfonic acid sodium with a mass ratio of 1:2.

[0045] The mass ratio of the modified alumina, FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O is 1:0.15:0.1:0.15; the hydrothermal reaction temperature is 160℃, and the time is 4h. Comparative Example 1

[0046] Al (NO3) 3·9H2O was dispersed in deionized water, and then a surfactant was added, and a precursor was obtained after mixing. Sodium hydroxide was added to the precursor to adjust the pH to 8, and after aging, centrifugation, washing, drying and calcination, modified alumina was obtained.

[0047] The modified alumina was ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O and La(NO3) 3·6H2O were added in sequence, and after mixing, hydrothermal reaction was carried out, and the product was obtained after cooling, centrifugation, washing and drying to obtain a photovoltaic wastewater treatment agent.

[0048] The mass ratio of Al (NO3) 3·9H2O and the surfactant was 1:0.05; the aging condition was: temperature 65℃, time 6h; the calcination condition was: temperature 500℃, time 3h, and the heating rate was 5℃ / min.

[0049] The surfactant was composed of male pimaric acid octadecyl amide double carboxylic acid sodium and itaconic acid-based unsymmetrical double ester sulfonic acid sodium with a mass ratio of 1:1.

[0050] The mass ratio of modified alumina, FeCl3·6H2O, ZrOCl2·8H2O and La(NO3) 3·6H2O was 1:0.1:0.08:0.1; the hydrothermal reaction temperature was 150℃, and the time was 6h. Comparative Example 2

[0051] Al (NO3) 3·9H2O and Ce(NO3) 3·6H2O were dispersed in deionized water, and then a surfactant was added, and a precursor was obtained after mixing. Sodium hydroxide was added to the precursor to adjust the pH to 8, and after aging, centrifugation, washing, drying and calcination, modified alumina was obtained.

[0052] The modified alumina was ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O and La(NO3) 3·6H2O were added in sequence, and after mixing, hydrothermal reaction was carried out, and the product was obtained after cooling, centrifugation, washing and drying to obtain a photovoltaic wastewater treatment agent.

[0053] The mass ratio of Al (NO3) 3·9H2O, Ce(NO3) 3·6H2O and the surfactant was 1:0.1:0.05; the aging condition was: temperature 65℃, time 6h; the calcination condition was: temperature 500℃, time 3h, and the heating rate was 5℃ / min.

[0054] The surfactant was male pimaric acid octadecyl amide double carboxylic acid sodium.

[0055] The mass ratio of modified alumina, FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O is 1:0.1:0.08:0.1; the temperature of hydrothermal reaction is 150℃, and the time is 6h. Comparative Example 3

[0056] Al(NO3)3·9H2O and Ce(NO3)3·6H2O are dispersed in deionized water, and then a surfactant is added, and after mixing, a precursor is obtained; sodium hydroxide is added to the precursor to adjust the pH to 8, and after aging, centrifugation, washing, drying and calcination, modified alumina is obtained.

[0057] The modified alumina is ultrasonically dispersed in deionized water, and then FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O are sequentially added, and after mixing, hydrothermal reaction is carried out, and the product is obtained after cooling, centrifugation, washing and drying.

[0058] The mass ratio of Al(NO3)3·9H2O, Ce(NO3)3·6H2O and the surfactant is 1:0.1:0.05; the aging condition is: temperature 65℃, time 6h; the calcination condition is: temperature 500℃, time 3h, and the heating rate is 5℃ / min.

[0059] The surfactant is itaconic acid-based unsymmetrical diester sodium sulfonate.

[0060] The mass ratio of modified alumina, FeCl3·6H2O, ZrOCl2·8H2O and La(NO3)3·6H2O is 1:0.1:0.08:0.1; the temperature of hydrothermal reaction is 150℃, and the time is 6h. Comparative Example 4

[0061] Al(NO3)3·9H2O and Ce(NO3)3·6H2O are dispersed in deionized water, and then a surfactant is added, and after mixing, a precursor is obtained; sodium hydroxide is added to the precursor to adjust the pH to 8, and after aging, centrifugation, washing, drying and calcination, modified alumina is obtained.

[0062] The modified alumina is ultrasonically dispersed in deionized water, and then ZrOCl2·8H2O and La(NO3)3·6H2O are sequentially added, and after mixing, hydrothermal reaction is carried out, and the product is obtained after cooling, centrifugation, washing and drying.

[0063] The mass ratio of Al(NO3)3·9H2O, Ce(NO3)3·6H2O and the surfactant is 1:0.1:0.05; the aging condition is: temperature 65℃, time 6h; the calcination condition is: temperature 500℃, time 3h, and the heating rate is 5℃ / min.

[0064] The surfactant is composed of sodium maleopimarate octadecylamide dicarboxylate and sodium itaconic acid-based asymmetric diester sulfonate in a mass ratio of 1:1.

[0065] The mass ratio of modified alumina, ZrOCl2.8H2O and La(NO3)3.6H2O is 1:0.13:0.15; the temperature of hydrothermal reaction is 150℃, and the time is 6h. Comparative Example 5

[0066] Al(NO3)3.9H2O and Ce(NO3)3.6H2O are dispersed in deionized water, and then a surfactant is added, and a precursor is obtained after mixing; sodium hydroxide is added to the precursor to adjust the pH to 8, and a modified alumina is obtained after aging, centrifugation, washing, drying and calcination.

[0067] The modified alumina is ultrasonically dispersed in deionized water, and then FeCl3.6H2O and La(NO3)3.6H2O are added in sequence, and the mixture is uniformly mixed and then subjected to hydrothermal reaction, and a photovoltaic wastewater treatment agent is obtained after the product is cooled, centrifuged, washed and dried.

[0068] The mass ratio of Al(NO3)3.9H2O, Ce(NO3)3.6H2O and the surfactant is 1:0.1:0.05; the aging condition is a temperature of 65℃ and a time of 6h; the calcination condition is a temperature of 500℃ and a time of 3h, and the heating rate is 5℃ / min.

[0069] The surfactant is composed of sodium maleopimarate octadecylamide dicarboxylate and sodium itaconic acid-based asymmetric diester sulfonate in a mass ratio of 1:1.

[0070] The mass ratio of modified alumina, FeCl3.6H2O and La(NO3)3.6H2O is 1:0.14:0.14; the temperature of hydrothermal reaction is 150℃, and the time is 6h. Comparative Example 6

[0071] Al(NO3)3.9H2O and Ce(NO3)3.6H2O are dispersed in deionized water, and then a surfactant is added, and a precursor is obtained after mixing; sodium hydroxide is added to the precursor to adjust the pH to 8, and a modified alumina is obtained after aging, centrifugation, washing, drying and calcination.

[0072] The modified alumina is ultrasonically dispersed in deionized water, and then FeCl3.6H2O and ZrOCl2.8H2O are added in sequence, and the mixture is uniformly mixed and then subjected to hydrothermal reaction, and a photovoltaic wastewater treatment agent is obtained after the product is cooled, centrifuged, washed and dried.

[0073] The mass ratio of Al (NO3) 3·9H2O, Ce (NO3) 3·6H2O and surfactant is 1:0.1:0.05; the aging condition is: temperature 65℃, time 6h; the calcination condition is: temperature 500℃, time 3h, and the temperature rising rate is 5℃ / min.

[0074] The surfactant is composed of maleopimaric acid octadecylamide double carboxylic acid sodium and itaconic acid-based asymmetric double ester sulfonic acid sodium with a mass ratio of 1:1.

[0075] The mass ratio of modified alumina, FeCl3·6H2O and ZrOCl2·8H2O is 1:0.15:0.13; the temperature of hydrothermal reaction is 150℃, and the time is 6h.

[0076] The treatment agent prepared by example 1 and comparative examples 1-6 is used to treat the wastewater of a certain photovoltaic factory, and the defluorination performance is measured, and the test results are shown in table 1.

[0077] The test method is: the treatment agent is made into a filter column, then the wastewater is passed into the filter column at a rate of 6m / h, the pH of the wastewater is 6.5, and the fluorine concentration in the wastewater before and after passing into the filter column is measured.

[0078] Table 1 defluorination performance test results

[0079] As can be seen from the experimental results of examples 1-3 in table 1, the treatment agent of the present application has excellent defluorination performance, wherein the treatment agent of example 1 can reduce the fluorine content in the wastewater to 0.4mg / L, meeting the discharge requirements.

[0080] As can be seen from the experimental results of example 1 and comparative example 1, in the preparation of modified alumina, the doping of cerium can further improve the defluorination performance of the treatment agent, because the introduced cerium salt as a doping source can form Ce-doped alumina material with oxygen vacancy structure in the subsequent calcination process. 3+ The reversible oxidation-reduction characteristics of Ce 4+ endow the material with excellent electron transfer ability, enhance the complexation and exchange ability of heavy metal ions; at the same time, the doping of cerium helps to improve the crystal structure stability of alumina particles, significantly improves its corrosion resistance and thermal stability in high acid-base environment, thereby prolonging the service life of the adsorbent in the photovoltaic wastewater treatment process. In addition, the addition of Ce element also increases the density of the surface acid sites of the adsorbent, and enhances its electrostatic adsorption ability to anions such as fluoride ions.

[0081] As can be seen from the test results of Examples 1 and Comparative Examples 2-3, the present application has a synergistic promotion effect on improving the fluorine removal performance of the treatment agent by introducing sodium maleopimarate octadecanamide dicarboxylate and sodium itaconic acid-based unsymmetrical diester sulfonate as surfactants into the precursor solution, because the surface modifier of the present application significantly improves the dispersibility of the particles and the pore structure regulation ability. The surfactant of the present application can inhibit particle agglomeration through steric hindrance and electrostatic repulsion effect on the one hand, so that the modified alumina nanoparticles have more uniform particle size and higher specific surface area; on the other hand, the surfactant can form weak coordination with metal ions, inducing the formation of a more ordered and synergistic skeleton structure in the hydrothermal reaction, thereby improving the multi-component synergistic adsorption performance of the subsequent composite material.

[0082] As can be seen from the test results of Examples 1 and Comparative Examples 4-6, the present application forms a Fe-Zr-La three-metal modification system by compounding modified alumina with iron salt, zirconium salt and lanthanum salt, which can generate a variety of active sites and composite oxide synergistic network on the surface of the material, further improving the fluorine removal performance of the treatment agent. Iron element mainly exists in the form of Fe(III) oxidation state, has excellent coordination ability and flocculation effect, and can effectively complex phosphorus, arsenic and organic complexes in wastewater; zirconium element has a high affinity for fluorine ions, and the Zr-OH functional group formed by its introduction can significantly enhance the specific adsorption of fluorine and phosphate; lanthanum, as a typical rare earth element, has adsorption selectivity for a variety of anions, and at the same time enhances the overall acid and alkali corrosion resistance of the material. The synergistic loading and distribution of the three on the modified alumina carrier make the surface of the material present a variety of functional sites, realize the multi-mechanism and high selectivity synergistic removal of fluorine in photovoltaic wastewater, and greatly improve the overall treatment efficiency and stability.

[0083] Although the embodiments of the present application have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, replacements and variations can be made to the embodiments without departing from the principles and spirits of the present application, the scope of the present application is defined by the appended claims and their equivalents, and all should be included within the protection scope of the present application.

Claims

1. A method for preparing a photovoltaic wastewater treatment agent, characterized in that, The steps are as follows: S1: Preparation of modified alumina; S2: Modified alumina is ultrasonically dispersed in deionized water, and then iron salt, zirconium salt and lanthanum salt are added in sequence. After mixing, a hydrothermal reaction is carried out. The product is cooled, centrifuged, washed and dried to obtain the photovoltaic wastewater treatment agent.

2. The method for preparing a photovoltaic wastewater treatment agent according to claim 1, characterized in that, The modified alumina is prepared as follows: S11: Disperse aluminum salt and cerium salt in deionized water, then add surfactant, mix well to obtain precursor; S12: Sodium hydroxide is added to the precursor to adjust the pH to 7.5-8.5, and modified alumina is obtained after aging, centrifugation, washing, drying and calcination.

3. The method for preparing a photovoltaic wastewater treatment agent according to claim 2, characterized in that, Aluminum salts are one or more of aluminum nitrate and its hydrate, aluminum chloride and its hydrate, and aluminum sulfate and its hydrate; One or more of the following: cerium salts: cerium nitrate and its hydrate, cerium chloride and its hydrate, and cerium sulfate and its hydrate.

4. The method for preparing a photovoltaic wastewater treatment agent according to claim 2, characterized in that, The mass ratio of aluminum salt, cerium salt and surfactant is 1:0.05-0.15:0.01-0.

1.

5. The method for preparing a photovoltaic wastewater treatment agent according to claim 2, characterized in that, The aging conditions are: temperature 60-70℃, time 4-8 hours; The calcination conditions are: temperature 400-600℃, time 2-4h, and heating rate 3-7℃ / min.

6. The method for preparing a photovoltaic wastewater treatment agent according to claim 2, characterized in that, The surfactant is composed of sodium maleic anhydride-octadecylamide-dicarboxylate and sodium itaconic acid-based asymmetric diester sulfonate in a mass ratio of 2:1-4.

7. The method for preparing a photovoltaic wastewater treatment agent according to claim 1, characterized in that, The mass ratio of modified alumina, iron salt, zirconium salt and lanthanum salt is 1:0.05-0.15:0.05-0.1:0.05-0.

15.

8. The method for preparing a photovoltaic wastewater treatment agent according to claim 1, characterized in that, The iron salt is one or more of the following: ferric nitrate and its hydrate, ferric chloride and its hydrate, and ferric sulfate and its hydrate; Zirconium salts are one or more of zirconium nitrate and its hydrate, zirconium chloride and its hydrate, and zirconium oxychloride and its hydrate; Lanthanum salts are one or more of lanthanum nitrate and its hydrate, and lanthanum chloride and its hydrate.

9. The method for preparing a photovoltaic wastewater treatment agent according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 140-160℃ for 4-8 hours.

10. A photovoltaic wastewater treatment agent, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of high efficiency Zr-Al-Ce based composite defluoridation material

    CN102357357A

  • Magnetic fluorine ion adsorbent and preparation method thereof

    CN104148004A

  • Magnetic crystal / non-crystal lanthanum-zirconium-iron oxide phosphorus removal adsorbent and synthesis method thereof

    CN110721654A

  • Preparation method and application of lanthanum-zirconium-iron composite oxide porous nanofiber

    CN114351290A

  • Water treatment fluorine removal agent as well as preparation method and application thereof

    CN119551788A

Cited By

  • Novel deep defluorination agent and resource application of solid waste generated by novel deep defluorination agent

    CN121554038A